Tracking Multimorbidity Changes in Diverse Racial/Ethnic Populations Over Time: Issues and Considerations. (5th February 2019) - Quiñones, Ana R; Allore, Heather G; Botoseneanu, Anda; Newsom, Jason T; Nagel, Corey L; Dorr, David A
Abstract: Multimorbidity is widely recognized as having adverse effects on health and wellbeing and may threaten the ability of older adults to live independently. Much of what is known about multimorbidity rests on research that has largely focused on one point in time, or from a static perspective. Given that there remains a lack of agreement in the field on how to standardize multimorbidity definitions and measurement, it is not surprising that analyzing and predicting multimorbidity development, progression over time, and its impact are still largely unaddressed. As a result, there are important gaps and challenges to measuring and studying multimorbidity in a longitudinal context. This Research Practice perspective summarizes pressing challenges and offers practical steps to move the field forward.